Investigation of the effects of melatonin on lung tissue through the NLRP3/TLR2/NEK7 pathway in an experimental endotoxemia model: Effects of melatonin on LPS induced lung injury - Tokat, Arif Osman; Öztürk, Osman; Okan, Aslı; Uçar, Sümeyye; Eroğlu, Ece; Doğanyi̇ği Züleyha; Ocak, Mert; Ateş, Şükrü; Yilmaz, Seher (Cellular and Molecular Biology, 2024)
Sepsis, a severe clinical syndrome, arises from pro-inflammatory and apoptotic processes. Its rapid progression from sepsis to severe stages necessitates timely intervention. The lipopolysaccharide (LPS) agent triggers pro-inflammatory mediator release through Toll-like receptors, particularly TLR-2, a vital biomarker in sepsis with multiple organ failure. In LPS-induced septic shock, the NEK7-mediated NLRP3 inflammasome pathway, linked to acute lung injury, is suppressed. This pathway is implicated in sepsis-induced platelet activation and septic shock development. Antioxidants like melatonin (MEL) may positively impact reducing septic shock. In microbial-induced sepsis, melatonin can regulate pro-inflammatory mediator transcriptional activation, potentially controlling the pro-inflammatory state. In the project, the histopathological impact of melatonin in lung tissue during endotoxic shock induced by the LPS agent in Sprague-Dawley rats, and its immunoreactivity to NLRP3/NEK7/TLR-2 molecules, were assessed. Lung volumes were evaluated using micro-computed tomography (Micro-CT). While bleeding, cell infiltration, and thickening of the alveolar wall were observed in the lungs of the LPS group, a reduction in these symptoms was noted in the MEL+LPS group. Expressions of NEK7, TLR2, and NLRP3 increased in both the LPS and MEL+LPS groups compared to the control group. It was determined that in the MEL+LPS group, levels of NEK7, TLR2, and Malondialdehyde (MDA) decreased compared to the LPS group. Additionally, a decrease in the total volume of lung tissue was observed in the LPS group. In this context, our study reported the therapeutic effect of melatonin on sepsis-related acute lung injury. Our study suggests that melatonin administration in the experimental endotoxemia model melatonin may help reduce lung damage by inhibiting NEK7 and TLR2 expressions.